2014
DOI: 10.1186/bf03352242
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional hybrid simulation of magnetized plasma flow around an obstacle

Abstract: The interaction between the magnetized plasma flow and an obstacle was investigated in the computer simulations described here by using a three-dimensional hybrid code (kinetic ions and massless fluid electrons). The results, which are relevant to the interaction between the solar wind and an unmagnetized planet (Venus or Mars), show that fundamental structures (bow shock and magnetotail) are formed. When a reflecting boundary is used at the obstacle, the magnetic field configuration was clearly asymmetrical i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 22 publications
3
29
0
Order By: Relevance
“…Plate lb shows that a magnetic barrier, where the magnetic field is larger than the typical value elsewhere, formed around the planet. These results are the same as those of Shimazu [1999] Plate 3c shows that the planetary oxygen ions escape into the solar wind on the lower side. They can escape from the planet and be picked up by the solar wind because their Larmor radius is larger than the width of the magnetic barrier.…”
Section: ] (5 X 1025supporting
confidence: 78%
See 3 more Smart Citations
“…Plate lb shows that a magnetic barrier, where the magnetic field is larger than the typical value elsewhere, formed around the planet. These results are the same as those of Shimazu [1999] Plate 3c shows that the planetary oxygen ions escape into the solar wind on the lower side. They can escape from the planet and be picked up by the solar wind because their Larmor radius is larger than the width of the magnetic barrier.…”
Section: ] (5 X 1025supporting
confidence: 78%
“…The other difference between the present simulation code and that of Shimazu [1999] is that there are twice as many grid cells in each direction. In the previous study of Shimazu [1999], fine structure in the shock could not be observed because of the sparse grid cells used.…”
Section: Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…Various hybrid simulation studies have been made of the solar-wind-ionosphere interaction of unmagnetized planets (Modolo et al, 2006(Modolo et al, , 2005Bößwetter et al, 2004;Janhunen, 2002, 2001;Shimazu, 2001Shimazu, , 1999Brecht, 1997;Brecht et al, 1993). The hybrid simulations treat ions as particles while electrons are considered as a massless charge-neutralizing fluid.…”
Section: Published By Copernicus Publications On Behalf Of the Europementioning
confidence: 99%